Agricultural research in Latin America and the Caribbean: A cross-country analysis of institutions, investment, and capacities - Stads, Gert-Jan; Beintema, Nienke M.; Pérez, Sandra; Flaherty, Kathleen; Falconi, César A. (International Food Policy Research Institute, 2016)
This report assesses trends in investments, human resource capacity, and research outputs in agricultural R&D—excluding the private (for-profit) sector—in LAC. It is an update of Stads and Beintema (2009), covering a more complete set of countries and focusing primarily on developments during 2006–2012/2013.1 The analysis draws largely from a set of country factsheets prepared by Agricultural Science and Technology Indicators (ASTI), which is led by the International Food Policy Research Institute (IFPRI), using comprehensive datasets derived from primary surveys and additional secondary sources targeting close to 700 agencies in 27 LAC countries.